Venous thromboembolism capture on electronic systems in obstetrics patients at St Thomas' Hospital. Issue 1 (19th October 2016) - Ahmad, Aminah Noor; Byrne, Megan Leyla; Imambaccus, Nazia; Hubert, Dawid; Gateley, Anna; Abdullahi Idle, Salwa; Lloyd, Jilly
Abstract : Venous thromboembolism (VTE) is one of the leading causes of maternal mortality in the UK. Therefore, timely VTE risk assessment is essential in all obstetrics patients. The Commissioning for Quality and Innovation (CQUIN) payment framework set a target for trusts to complete a VTE risk assessment within 24 hours of admission for 95% of patients. A combination of factors, including lack of integration between multiple IT systems, means that this CQUIN target is currently not being met for obstetric patients in the Hospital Birth Centre at Guys and St Thomas' NHS Trust. This project aims to increase staff awareness of this issue and educate them regarding the correct procedure for VTE assessment. Trialled methods included reminders at staff handovers, use of magnets on the patient whiteboard, posters and stickers displayed around the unit and a loyalty card scheme as incentive to complete assessments. Initial average completion rate was 20.7%, which increased to 67.5% after the first plan, do, study, act (PDSA) cycle with a slight drop to 65.7% after the second cycle. Completion rates increased to 92.3% on the last day of the third PDSA cycle. Although we did not reach the 95% target, we have raised awareness of the importance of recording VTE assessment on electronic systems, and hope we have created sustainable change.